Aktualisasi Nilai Akhlak Melalui Pembiasaan Menghafal Hadis Pendek Di MI Roudlotus Shibyan Beton Menganti Gresik - Siti Khotijah; Mulyadi (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2021)
There is a moral decline among students in the world of education. This is because one of them is the development of increasingly sophisticated science and technology, but this development is not balanced with the cultivation of moral values ​​as the foundation of students in dealing with these developments. Moral corruption has become an epidemic among madrasas, they do not get used to praying five times a day, speak impolitely, when they meet the teacher they do not say hello and do not obey their elders or teachers. With the habit of memorizing short hadiths, students will know the content in the hadith. For example, there is a hadith about doing good, so students will understand that we have to do good. The problems to be answered through this research are: a) How is the actualization of moral values ​​through the habit of memorizing short hadiths b) What are the obstacles experienced in the habit of memorizing short hadiths? The method used is qualitative in the form of case studies. Data collection techniques were carried out through observation, interviews and documentation. Data were analyzed by reducing, presenting and drawing conclusions. The results showed that the habit of memorizing short hadiths was carried out every day by all students every morning before the lesson began, by the way the teacher appointed 2 or 3 students to come forward, and read the hadiths and imitated other students. The obstacles experienced were students and teachers who were late, students who were afraid, and lack of discipline in line. From these obstacles, madrasas take action to always accompany, direct and encourage students, so that they can follow the habit of memorizing short hadith well.